2014
DOI: 10.5194/bg-11-5637-2014
|View full text |Cite
|
Sign up to set email alerts
|

Transport of branched tetraether lipids from the Tagus River basin to the coastal ocean of the Portuguese margin: consequences for the interpretation of the MBT'/CBT paleothermometer

Abstract: Abstract. Branched glycerol dialkyl glycerol tetraethers (brGDGTs), which are thought to be transported from soil to marine sediment by rivers, have been used to reconstruct the mean annual air temperature (MAAT) and soil pH of the drainage basin using the methylation index of branched tetraethers (MBT, recently refined as MBT') and cyclization index of branched tetraethers (CBT) from coastal marine sediment records. In this study, we trace the brGDGTs from source to sink in the Tagus River basin, the longest … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 74 publications
7
33
0
Order By: Relevance
“…However, the concentrations of CL crenarchaeol in soils were in general higher with increasing soil pH (>7, Figure 8B), resulting in lower BIT values ( Figure 8C). This is in good agreement with previous studies which showed that soil pH was positively related to CL crenarchaeol concentrations and thus negatively associated with BIT values (e.g., Weijers et al, 2006b;Kim et al, 2010;Yang et al, 2011;Zell et al, 2014a). It has been previously suggested that soil pH might more strongly influence the occurrence of the source organisms producing crenarchaeol than those producing brGDGTs (Kim et al, 2010).…”
Section: Discussion Abundance and Distribution Of Gdgts In Soilssupporting
confidence: 92%
See 4 more Smart Citations
“…However, the concentrations of CL crenarchaeol in soils were in general higher with increasing soil pH (>7, Figure 8B), resulting in lower BIT values ( Figure 8C). This is in good agreement with previous studies which showed that soil pH was positively related to CL crenarchaeol concentrations and thus negatively associated with BIT values (e.g., Weijers et al, 2006b;Kim et al, 2010;Yang et al, 2011;Zell et al, 2014a). It has been previously suggested that soil pH might more strongly influence the occurrence of the source organisms producing crenarchaeol than those producing brGDGTs (Kim et al, 2010).…”
Section: Discussion Abundance and Distribution Of Gdgts In Soilssupporting
confidence: 92%
“…However, the CL DC values in the marine surface sediments were slightly higher than those of the lower Rhône SPM (Figure 9E), showing a similar trend with increasing distance offshore as for the concentrations of CL brGDGTs. Similar studies carried out in other river systems also revealed an increase in the CL DC from soils to the marine environment for a Svalbard fjord (Peterse et al, 2009a), the lower Yangtze River-East China Sea shelf (Zhu et al, 2011), the Pearl River estuary , the Portuguese margin (Zell et al, 2014a), and the Amazon shelf (Zell et al, 2014b). This increase in the DC was assumed to be due to in situ production of brGDGTs in the marine environment, since the pH of the marine environment (pH ≈ 8) is usually higher compared to that of soils and river water.…”
Section: Sources Of Gdgts In Marine Surface Sedimentssupporting
confidence: 75%
See 3 more Smart Citations